Tree cover in the early Holocene in temperate Europe and implications for the practice of re-wilding in nature conservation - Baker, A (2014)
This thesis addresses the methodological challenges of determining the variability of large herbivore populations through time and their impact on European vegetation. Large herbivores are at the heart of conservation policy. However, opinions widely diverge on whether we should aim for fewer herbivores and managed populations or, on the contrary as advocated by the rewilding movement, more herbivores and self-regulating populations acting as ecosystem engineers. This controversy has roots in a debate regarding the nature of ecosystems before the prevalence of human activities. Baseline ecosystems are either described as continuous forest cover with passive large herbivores, or, in contrast, as mosaics with patchy forest cover driven inter alia by bison, aurochs and horses, now rare or extinct in Europe. The main obstacle in moving this debate forward is a poor understanding of large-herbivore densities in the past. I analysed modern pollen and spore assemblages from known environmental settings to improve palaeoecological interpretation of fossil assemblages dating from the pre-human (baseline) period. The sites investigated are the rewilded grasslands of the Oostvaardersplassen (The Netherlands), the mosaic habitats of The New Forest (UK) and the old-growth closedcanopy forest of Białowieża (Poland). I demonstrate that the common practice of interpreting pollen percentages fails to estimate past forest cover in situations with natural grazing. As an explanation, I suggest that pollen productivity fluctuates with biotic factors such as herbivory and canopy shading. As a result, new insights into the baseline debate require additional lines of evidence. In this thesis, I develop an existing methodology to reconstruct past herbivore presence using fossil dung fungal spores. I synthesise current knowledge of this method with an emphasis on spore identification and, finally, I demonstrate that dung fungal spore abundance in lake sediments can be translated into large herbivore numbers. The evidence presented in this thesis contributes to the debate on re-wilding and addresses a fundamental challenge of nature conservation in the human-dominated landscapes of Europe.